ANALYSIS OF VIBRATION SIGNATURE IN DEEP GROOVE BALL BEARING USING FINITE ELEMENT METHOD - G Keni, Laxmikant; Padmaraj N H; Khan , Najiullah; P E, Jagadeesha; R, Pradeep; K N, Chethan (Journal of Applied Engineering Science, 2022)
The most common kind of bearing is the rolling element bearing, which is a used mechanical component in rotating equipment that is subjected to heavy loads and rapid rotation. Bearing failure is the main consideration in the failure of rotating hardware. A deformity at any component of the bearing transmits to every single other component, for example, external race, inward race, ball, and retainer of the bearing. The simplest way to think about ball bearing failure examination is to create counterfeit cracks of varying sizes on various components of CATIA V-6 and write down their signatures. For this reason, the vibration investigation procedure which is dependable and precisely recognizing deformity in the bearing components is utilized. Estimation of the amplitude of vibrations is carried out at 5000 RPM, a load of 200 N, and at different deformity sizes, 3 mm and 4 mm on bearing races are carried out. A preparatory vibration investigation of a rolling component is carried out using Ansys R-18.0. Vibration signals for two diverse imperfection sizes have been extricated and a file for correlation of various deformity sizes has been proposed. The impacts of radial load, rotation speed, and starting deformity size on the stress level are studied.